In Search for a Smoking Gun: What Makes Income Inequality Vary Over Time in Different Countries? - Björn A. Gustafsson; Mats Johansson (Luxembourg Income Study (LIS), 1997)
Forces affecting the development of the distribution of income in OECD-countries are investigated by analyzing an unbalanced panel with information covering 16 countries from 1966 to 1994. Income inequality is measured with the Gini-coefficient of equivalent disposable income. The results suggest that many factors affect the development of inequality. Factors are strictly economic or outside a strictly defined market-sphere as well as being demographic. However, a relation between the unemployment rate and inequality could not be found.
Keywords: 330; Einkommensverteilung; OECD-Staaten